Respuesta :

Answer:

f(4) = 24

Step-by-step explanation:

Plug in 4 for x in the equation:

f(x) = x² + 3x - 4

f(4) = (4)² + 3(4) - 4

Remember to follow PEMDAS. PEMDAS =

Parenthesis

Exponents (&  Roots)

Multiplication

Division

Addition

Subtraction

and is the order of operation.

First, solve the power:

(4)² = 4 * 4 = 16

Next, multiply 3 with 4:

3 * 4 = 12

Next, combine the terms:

f(4) = 16 + 12 - 4

f(4) = (16 + 12) - 4

f(4) = 28 - 4

f(4) = 24

f(4) = 24 is your answer.

~

Answer:

24

Step-by-step explanation:

Plug x as 4.

(4)² + 3(4) - 4

16 + 12 - 4

= 24

ACCESS MORE